DUMBARTON OAKS CONFERENCE IN 1944 AND ITS INFLUENCE ON THE DEVELOPMENT OF INTERNATIONAL RELATIONS IN THE ANTI-HITLER ALITION - T. V. Kashirina (Гуманитарные и юридические исследования)
The article studies cooperation of the anti-Hitler coalition on the issue of the creation of the United Nations. The analysis is performed on the basis of documents presented by representatives of the USSR, the USA and Great Britain at the international conference held at Dumbarton Oaks in 1944. The focus is on the issues on which agreement had been reached between the Allied Powers, as well as the issues on which differences emerged. First and foremost is the question of membership and voting in the UN Security Council. The conclusion about the importance of the meeting at Dumbarton Oaks is made as it contributed to the development of cooperation between the powers of the antiHitler coalition during World War II.